The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1046/j.1365-2982.2000.00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Fedotozine, a kappa‐opioid agonist, prevents spinal and supra‐spinal Fos expression induced by a noxious visceral stimulus in the rat

Abstract: Fedotozine, a kappa opioid agonist, reverses digestive ileus caused by acetic acid (AA)-induced visceral pain in rats. The aims of this study were: to map, in conscious rats, central pathways activated by AA using Fos as a marker of neuronal activation; to characterize primary afferent fibres involved in this activation; and to investigate the effect of fedotozine on AA-induced Fos expression. AA (0.6%; 10 mL kg-1) was injected i.p. in conscious rats either untreated; pretreated 14 days before with capsaicin; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 66 publications
(97 reference statements)
4
25
0
Order By: Relevance
“…Because induction of c-FOS expression is widely used as an index of nociception and activation of afferent pathways (Bonaz et al, 2000), our data support the notion that H 2 S functions as a neuromodulator that participates in the inhibitory modulation of visceral nociception in the CNS.…”
Section: Discussionsupporting
confidence: 72%
“…Because induction of c-FOS expression is widely used as an index of nociception and activation of afferent pathways (Bonaz et al, 2000), our data support the notion that H 2 S functions as a neuromodulator that participates in the inhibitory modulation of visceral nociception in the CNS.…”
Section: Discussionsupporting
confidence: 72%
“…In animal models of acute (Bonaz et al, 2000) and chronic (Julia et al, 1995) inflammation, abnormal pain responses to CRD have been observed, demonstrating that inflammation induces both hyperalgesia and allodynia that persist when local inflammation is partially or totally resolved. Human studies in patients with ulcerative colitis and Crohn's disease (Bernstein et al, 1996;Chang et al, 2000) and IBS (Collins et al, 2001) have confirmed that colonic inflammation modulates colonic neural afferents.…”
Section: Discussionmentioning
confidence: 99%
“…Fos, the protein product of the immediate early gene c-fos is a sensitive marker of neuronal activation classically used to localize 3 V. Sinniger et al spinal cord neurons responsive to acute stimuli of somatic or visceral origin (Menetrey et al, 1989;Hunt et al, 1987;Herdegen et al, 1991;Traub et al, 1992Traub et al, , 1993. Using the model of somatovisceral pain, we have previously shown that, fedotozine, a kappa-opioid receptor agonist known to improve abdominal symptoms in IBS patients (Dapoigny et al, 1995;Delvaux et al, 1999), has an antinociceptive effect and prevents AA-induced Fos expression in the thoraco-lumbar spinal cord in rats through a peripheral action on visceral afferents (Bonaz et al, 2000).…”
Section: Intracolonic (Ic) Instillation Of Trinitrobenzenesulfonic Acmentioning
confidence: 99%
“…Somato-visceral pain was assessed by counting abdominal contractions (Koster et al, 1959;Giamberardino et al, 1995;Bonaz et al, 2000) for 60 minutes, by periods of 10 min, following the ip injection of AA, classically described as the writhing test (Koster et al, 1959). Abdominal contractions consisted of the contraction of the flank muscles associated with inward movements of the hindlimb or with whole body stretching (Giamberardino et al, 1995).…”
Section: Noxious Somato-visceral Stimulusmentioning
confidence: 99%
See 1 more Smart Citation